TEACHING MATERIAL FOR ENGLISH SUBJECT IN VOCATIONAL HIGH SCHOOL - Okri Ronaldo (Universitas Negeri Padang, 2016)
The purpose of this study is to evaluate the teaching material of English subject at Vocational High School by referring to ESP approach because, theoretically, teaching English in Vocational High School should relate and support the specific skill which is studied by its students. This is descriptive research by using qualitative inquiry. This study was conducted in SMK N 2 Sijunjung where the sources of data is the teaching material that be given by the English teachers to their students in academic year 2014/2015. After analyzing the data, it was found that English teaching material in SMK N 2 Sijunjung does not follow of ESP approach for each specific study in that school yet. The data show that most of content and context of teaching material are still too general for Vocational High School students. It can be concluded that the implementation of ESP in Vocational High School could not run well yet. Hence, the practitioner and English teacher are expected to develop English teaching material for Vocational School students that relate and support their certain skill in order to make their English competence could help their career in the future. In addition, it also stimulus them in learning English because teaching material which given in the English class relate to their topic in their specific study in the workshop or laboratory.